Designing Lateral Thoracic Wall Perforator Flaps for Breast Reconstruction Using Ultrasound - Salgarello, Marzia; Visconti, Giuseppe (Journal of Reconstructive Microsurgery, 2021)
Background Lateral thoracic flaps represent a precious source for partial and total breast reconstruction, in some cases as first option and in other cases as alternative of free flaps. This article describes the ultrasound (US)-based planning of the lateral thoracic wall perforator adipocutaneous flaps and it reports our experience on 52 consecutive flaps.Methods From November 2018 to May 2021, 52 consecutive lateral thoracic wall perforator flaps were performed using the US-based method for reconstruction of partial breast defects and total breast reconstruction. High-frequency US was performed in all cases prior to surgery to select the best perforator and design the flap.Results Of the 52 cases, 41 were lateral intercostal artery perforator flaps (78.8%), and 11 were thoracodorsal artery perforator (TDAP) flaps. Of the 11 TDAP flaps, 2 cases were based on the direct cutaneous branch. Moreover, in two other cases clinically scheduled for lateral thoracic perforator flaps due to the presence of an appropriate axillary roll, no suitable local/regional perforators were detected with the preoperative US examination and the latissimus dorsi myocutaneous flap was performed.Conclusion Preoperative planning of these flaps using US speeds the surgery and makes it easier and more efficient. Therefore, it is reasonable that the color duplex ultrasound is the operative surgeon's tool for mapping the lateral thoracic wall perforators and to appropriately plan each flap.
Keywords: intercostal perforator flap; thoracodorsal perforator flap; perforator breast reconstruction